Pelatihan Pembuatan Dasar Gerakan Matematika - Mahmudah, Muhlisatul; Novita Irawati, Tri; Septy Arifannah, Dwi; Sri Wahyuni, Linda; Khoirunnisa, Najhan; Agustin Reni Pitasari, Mely (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Basic math movement training was conducted with the aim of providing fun learning innovations for students while enhancing teacher creativity in teaching. This activity uses a hands-on approach through the creation of simple movements integrated with basic mathematical concepts. The training was attended by teachers and students at MIS Darul Mustofa Panti, Jember, in September 2025. The results showed that teachers gained new insights in developing interactive methods, while students experienced a more enjoyable and meaningful learning experience. Thus, math movement has the potential to become an alternative, creative learning strategy and can be implemented sustainably in other schools.